The Effect of Leaflet Media Health Counseling on Public Knowledge about the Implementation of the Covid-19 Health Protocol - Hadid Al Hafidz; Nova Mega Rukmana; Achmad Djamil (Global Health Science Group, 2021)
The Corona Virus Health Protocol 2019 (Covid-19) is a policy set by WHO as the World Health Organization and by the Government of Indonesia to overcome the Covid-19 pandemic. This study aims to identify the effect of leaflet media health counseling on public knowledge about the implementation of covid-19 health protocol in LK 06 Kelapa Tujuh, North Lampung. This research is really important as kind of prevention to face this pandemic because no one knows when will this pandemic end. The aim is to find out public knowledge about the Covid-19 health protocol before and after being given counseling. The type of research used is quantitative research with Tr ue Experiments research design using the Pretest-Posttest Control Group Design approach. The population is the head of the family in the LK 06 Kelapa Tujuh with the sample criteria being traders. The research instrument use a questionnaire sheet with validity test obtained R Table of 0.444. The statistical test use the Independent Samples t Test. The results show that, based on the answers to the knowledge and behavioral application questionnaire, the results of the Independent Samples t Test show that the Sig value or p value = 0.000 is smaller than 0.05. So, it can be concluded that there is an influence from Leaflet Media Health Counseling on Public Knowledge about the Implementation of the Covid-19 Health Protocol.